Grind or Gamble? An Experimental Analysis of Effort and Spread Seeking in Contests - Ola Andersson; Håkan J. Holm; Erik Wengström (Lund University, School of Economics and Management, Department of Economics, 2019)
We conduct a contest experiment to study if spread seeking and effort can be managed in a situation where participants can invest in increasing both the mean and the spread of an uncertain performance variable. Subjects are treated with different prize schemes and in accordance with theory, we observe substantial investments in spread for the winner-take-all scheme. Both types of investments can be controlled with a three-level prize scheme. However, the control management is imperfect and behavior is characterized by inertia. The winner-take-all prize scheme has many potential disadvantages including high spread and heterogeneous behavior compared to other schemes.
Keywords: C70; D02; D03; D80; 330; Contest; Risk; Spread; Incentives; Institutional Choice; Experiment